INSOMNIA DISORDER IN PRIMARY CARE: DIAGNOSIS AND EVIDENCE-BASED MANAGEMENT - Spychalska, Weronika; Krawczyk, Aleksandra; Roszak, Jakub; Sumlet, Paulina; Kurasińska, Wiktoria; Witowicz, Filip; Glińska, Julia; Waldon, Wiktoria; Chmielewska, Zuzanna; Kaźmierkiewicz, Roch (International Journal of Innovative Technologies in Social Science, 2026)
Chronic insomnia disorder affects approximately one in ten adults in Europe. Despite this prevalence, it remains substantially underdiagnosed and undertreated in primary care, where pharmacotherapy is prescribed far more frequently than the evidence-based first-line intervention, cognitive behavioural therapy for insomnia (CBT-I) [8,12]. In Poland, subjective insomnia is reported by approximately 50.5% of the adult population (58.9% in women, 41.4% in men) [6]. Estimates of clinically defined insomnia disorder vary depending on the diagnostic criteria applied. This narrative review provides primary care physicians with a practical framework for the diagnosis and management of chronic insomnia disorder. Recommendations are drawn from four current guidelines: the European Insomnia Guideline 2023 [8], the VA/DoD Clinical Practice Guideline 2025 [3], the AASM Behavioural Treatment Guideline 2021 [2], and the Polish recommendations of the PTBS, PTMR, and PTP 2023 [1]. Diagnosis relies on clinical grounds alone [3,8]. Before initiating treatment, a structured five-domain differential evaluation should be completed- covering mental health, somatic conditions, medications, lifestyle, and primary sleep disorders. CBT-I, delivered face-to-face or via validated digital platforms, is the consistently recommended first-line treatment across all major current guidelines. Its effects are durable in a way that pharmacotherapy alone cannot replicate [2,8]. When pharmacological treatment is required, it should be short-term and dose-minimised. Agent selection should be guided by patient age, comorbidities, and dependence risk. Dual orexin receptor antagonists represent an option with a favourable dependence profile and European Medicines Agency (EMA) approval for chronic insomnia [1,3,4,8]. Structured deprescribing of chronically used hypnotics, supported by concurrent CBT-I, should be integrated into routine primary care practice [5].